2017
DOI: 10.1002/cphc.201700202
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Protonated Model Disaccharides from Tandem Mass Spectrometry and Chemical Dynamics Simulations

Abstract: The fragmentation mechanisms of prototypical disaccharides have been studied herein by coupling tandem mass spectrometry (MS) with collisional chemical dynamics simulations. These calculations were performed by explicitly considering the collisions between the protonated sugar and the neutral target gas, which led to an ensemble of trajectories for each system, from which it was possible to obtain reaction products and mechanisms without pre‐imposing them. The β‐aminoethyl and aminopropyl derivatives of cellob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 86 publications
1
10
0
Order By: Relevance
“…The use of additional gas phase analytical approaches coupled to mass spectrometry has added new levels of information that have been effective for studying carbohydrate structure. Isotopic labeling strategies 7, 11, 1519 and gas-phase infrared spectroscopy 2024 together with molecular modelling 20, 2527 have provided valuable insights into the structures of a wide range of carbohydrate ions. Ion mobility spectrometry with mass spectrometry (IM-MS) is fast emerging as a powerful tool for characterizing biological molecules and has been gaining ground in recent years for resolving, identifying, and structurally characterizing glycans 25, 2833 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of additional gas phase analytical approaches coupled to mass spectrometry has added new levels of information that have been effective for studying carbohydrate structure. Isotopic labeling strategies 7, 11, 1519 and gas-phase infrared spectroscopy 2024 together with molecular modelling 20, 2527 have provided valuable insights into the structures of a wide range of carbohydrate ions. Ion mobility spectrometry with mass spectrometry (IM-MS) is fast emerging as a powerful tool for characterizing biological molecules and has been gaining ground in recent years for resolving, identifying, and structurally characterizing glycans 25, 2833 .…”
Section: Introductionmentioning
confidence: 99%
“…First studies focusing on energy transfer used molecular mechanics potential, [19] while later semi‐empirical Hamiltonians, density functional theory or MP2 methods were used [14] . To study relatively large ions, semi‐empirical Hamiltonians are necessary and recent studies suggest that PM3, RM1, PM6‐D or PM7 show the best performances [12,14c–e,20] . For V ion/neutral it is possible to use analytical functions, parametrized on accurate quantum chemistry calculations, [14b,e,19,20b,21] while semi‐empirical Hamiltonians are well performing for N 2 [22]…”
Section: Methodologiesmentioning
confidence: 99%
“…In both cases, the VENUS code coupled with MOPAC was used to propagate the dynamics based on the PES computed on-the-fly at the PM3 level. Even if other semiempirical Hamiltonians are available, PM3 was recently shown to be able to correctly reproduce CID of some peptides and negative ions. Because the aim of the present study is not a method comparison in reaction dynamics, here we report PM3-based results that are directly compared with experiments.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…When using trajectories to understand CID experiments, one needs to consider an ensemble of trajectories for reasons of statistical sampling, so that high-level theoretical methods cannot be employed due to the excessive computational cost that would be required. Nevertheless, it has been shown that semiempirical Hamiltonians offer a valuable tool to understand the fragmentation of amino acids and peptides, sugars, , and other relatively large organic molecules (e.g., uracil , and testosterone). These types of simulations have also been used to understand isomerization and fragmentation mechanisms.…”
Section: Introductionmentioning
confidence: 99%